Avaliação da atividade antifúngica dos compostos cumarínicos frente às cepas do gênero aspergillus. - Guerra, Felipe Queiroga Sarmento (2016)
In recent decades fungal infections have increased, and their high rates of morbidity and mortality have brought them much attention. Immunocompromised patients are more susceptible to microorganism infections; in particular, fungal species of the genus Aspergillus spp. Among the current infectious filamentous fungi they have a rather high incidence. Antifungal treatments have been subjected to numerous studies, and the increasing number of resistant fungal species has been highlighted. Thus, we see the importance of seeking new, more effective, and less toxic therapeutic sources. The aim of this study was to evaluate the in vitro antifungal activity and structure activity relationships of coumarin compounds against Aspergillus species. For this the MIC of 24 coumarin compounds was determined and subsequent SAR studies were performed with computer software. 12 of the 24 tested coumarin derivatives have antifungal activity, with 5 has shown excelent activity. Thus two derivatives, 7-hydroxy-6-nitrocoumarin (Cou-UNO2), and 4-acetoxycoumarin (Cou-UMB16), with better MIC values were evaluated via inhibition of mycelial growth and conidial germination, and by mechanism of action testing. The products were evaluated in combination with antifungals standards. The results showed that 12 of the 24 tested coumarin derivatives have antifungal activity, with MIC values ranging from 1024-16μg/ml. SAR studies have showed that the presence of a short aliphatic chain, and/or electronegative groups like ring substituents are favorable for antifungal activity. The coumarin derivatives with better MIC values (16μg/ml); Cou-UNO2 and Cou-UMB16 were capable of inhibiting both the mycelial growth and conidial germination of Aspergillus spp. Their activity is on the structure of the fungal cell wall. Cou-NO2, in a sub-inhibitory concentration, enhanced the in vitro effects of azoles, and in combination with azoles (voriconazole and itraconazole) there was an additive effect. Cou-UMB16 in combination with azoles (voriconazole and itraconazole) had synergistic or additive effects depending on the strain used. Thus this study concludes that coumarin derivatives have antifungal activity against the species A. flavus and A. fumigatus. The coumarin Cou-UMB16 and Cou-UNO2 have able to inhibit the mycelial growth and conidio germination and that this activity is due to its action on the fungal cell wall and the presence of electronegative groups as substituents of the benzopyrone ring favors this activity.